Revisiting nuclear policies under Modi regime: Leadership analysis and repercussions for Pakistan - Muhammad Umer Hayat; Aleena Zaid (Masyarakat, Kebudayaan dan Politik, 2021)
Modi’s leadership and governance pattern is a matter of consideration as concerned directly with styles of functioning of his adopted policies, which reflects his undertakings both in the social and political realm. This paper seeks to offer an alternative perspective in the domain of the rising threat of Hinduism, while the consolidation of the political power in India has been raising serious implications for Pakistan, in particular. It highlights the impact of all such harsh realist nuclear policies that may cause more complexities and further deteriorate the region's stability. This study deployed descriptive, analytical, and explanatory research techniques but to great extent, a major part consists of the descriptive study, which will be used when it comes to genesis and existing various scenarios. Findings also substantiate India’s intentions and the propaganda waged and all steps keenly targeting Pakistan. Bharatiya Janata Party (BJP) seems to be adopting new realist approaches deeply rooted with that of Kautilya’s. Therefore, the paper concludes that the rise of Hindu nationalists gets the support of Rashtriya Swayamsevak Sangh (RSS)-based concept demanding soft measures to lessen the worrisome environment causing by the Modi regime.